2019
DOI: 10.1002/jssc.201900339
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitative analysis of polyphenolic compounds in human plasma by liquid chromatography tandem mass spectrometry

Abstract: A diet rich in polyphenolic compounds has recognized health benefits, and as such is routinely monitored as part of dietary intervention studies. A method for the simultaneous determination of 36 phenolic compounds, including phenolic acids and flavonoids, using liquid chromatography and tandem mass spectrometry is described here. The target analytes were quantified based on their specific mass spectral fragments using a selected reaction monitoring approach. A C18 column with embedded aromatic functionality e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Different methods have been reported in the literature for determination of phytochemicals via HPLC, MS, UV, etc. [38][39][40][41][42][43]. Moreover the GC-MS provides scientific world a more economic and efficient option to scrutinize key fermentation products such as volatile fatty acids, acetic acid, esters, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been reported in the literature for determination of phytochemicals via HPLC, MS, UV, etc. [38][39][40][41][42][43]. Moreover the GC-MS provides scientific world a more economic and efficient option to scrutinize key fermentation products such as volatile fatty acids, acetic acid, esters, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, the solubility of TMCA was much lower in some solvents, which limited its industrial application. In previous reports, to obtain higher purity TMCA, high-performance liquid chromatography (HPLC), HPLC/mass spectrometry (HPLC/MS), and other methods were utilized to separate . It is of great scientific value to explore the solubility of TMCA in different solvents and select the appropriate solvent for dissolution or crystallization, providing convenience for future research and application of TMCA.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, to obtain higher purity TMCA, high-performance liquid chromatography (HPLC), HPLC/mass spectrometry (HPLC/MS), and other methods were utilized to separate. 13 It is of great scientific value to explore the solubility of TMCA in different solvents and select the appropriate solvent for dissolution or crystallization, providing convenience for future research and application of TMCA. At present, the relative literature studies available for reference on the solubility data of TMCA are not reported to provide a great reference for TMCA industrial production; the common organic solvents (methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, methyl acetate, ethyl acetate, acetonitrile, and acetone) and water in the pharmaceutical and chemical industries were selected for the crystallization experiment with the temperature range (278.15−323.15 K) in this work.…”
mentioning
confidence: 99%